The shifting regional geopolitics of Mekong dams. (March 2016) - Hirsch, Philip
Abstract: The Mekong is a region whose geopolitics are shifting in complex ways. They are shifting with the post-Cold War reconfiguration of ideological as well as strategic power deployments. They are also shifting with rapid economic development and associated regional integration. This paper employs these various dimensions of shifting geopolitics to explore and partially explain the (re)emergence of hydropower development in the Mekong. It does so by outlining both the shifting geopolitics of river and region, and showing how the Mekong as metaphor extends to much more than the materiality of the river from which the multiply constructed region derives its name. It suggests that the regional geopolitics produced by these shifts is key to the re-emergence of mainstream hydropower.